FRI0456 Predictors for disease worsening defined by organ failure in diffuse systemic sclerosis: a european scleroderma trials and research (EUSTAR) analysis. (12th June 2018) - Becker, M.O.; Graf, N.; Sauter, R.; Allanore, Y.; Curram, J.; Denton, C.; Khanna, D.; Matucci-Cerinic, M.; Pena, J.; Pope, J.E.; Distler, O.
Abstract : Background: Mortality and worsening of organ function are desirable endpoints for clinical trials in systemic sclerosis (SSc). However, these events are relatively rare, making clinical trial design challenging. Objectives: To identify factors in a population of patients with diffuse SSc from the European Scleroderma Trials and Research (EUSTAR) group database that predict these endpoints and hence allow enrichment of those patients. Methods: Inclusion criteria were a diagnosis of diffuse SSc and follow-up after 9–15 (12±3) months. This timeframe was chosen to reflect typical clinical trial design. Disease worsening/organ progression was fulfilled if any of the following events occurred: new renal crisis, decrease in forced vital capacity (FVC) ≥10%, new left ventricular ejection fraction (LVEF) <45% or decrease in LVEF by >10% for patients with baseline LVEF <45%, new pulmonary (arterial) hypertension, or death. These parameters had been defined by expert nominal group technique. Methodologically, two main limitations had to be addressed: 1 the problem of missing data and 2 the low number of events, which prohibits the simultaneous exploration of a large set of predictors in a regression model. We addressed these issues by (a) imputing multiple predictors based on different algorithms (multiple imputation), and (b) using least absolute shrinkage and selection operator (LASSO) regression for 42 clinical parameters. Results: Of 1451 patients who met the inclusion criteria, 706 had complete data available on all parameters for disease worsening. Of 706 patients originally evaluated, 228 (32.3%) had disease progression, most of which was either a decrease in FVC (103 patients, 14.6%) or death (92 patients, 13.0%) within the observation period (12±3 months). Of the 42 clinical parameters introduced into the model as outcome predictors, 8 remained in the final regression model, which was chosen by the Bayesian information criterion (table 1). Bootstrap with 10 000 repetitions successfully validated the model. Conclusions: The use of the predictive factors presented here could enable cohort enrichment with patients at risk for overall disease worsening in clinical trials. Acknowledgements: This study was supported by Bayer AG (Berlin, Germany). Disclosure of Interest: M. Becker: None declared, N. Graf: None declared, R. Sauter: None declared, Y. Allanore Grant/research support from: Actelion Pharmaceuticals US, Bayer AG, Bristol-Myers Squibb, Inventiva, Medac, Pfizer Inc, Roche Pharmaceuticals, Genentech and Biogen IDEC Inc. Sanofi-Aventis Pharmaceutical, Servier, Consultant for: Actelion Pharmaceuticals US, Bayer AG, Bristol-Myers Squibb, Inventiva, Medac, Pfizer Inc, Roche Pharmaceuticals, Genentech and Biogen IDEC Inc., Sanofi-Aventis Pharmaceutical, J. Curram Shareholder of: Bayer AG, Employee of: Bayer Plc, C. Denton Consultant for: Actelion Pharmaceuticals US, Bayer AG, GlaxoSmithKline, CSL Behring, Merck-Serono, Roche Pharmaceuticals, Genentech and Biogen IDEC Inc., Inventiva, Sanofi-Aventis Pharmaceutical, Boehringer Ingelheim, Speakers bureau: Actelion Pharmaceuticals US, Bayer AG, GlaxoSmithKline, CSL Behring, Merck-Serono, Roche Pharmaceuticals, Genentech and Biogen IDEC Inc., Inventiva, Sanofi-Aventis Pharmaceutical, Boehringer Ingelheim, D. Khanna Shareholder of: Eicos, Grant/research support from: Bayer, Bristol-Myers Squibb, Boehringer Ingelheim, Genentech/Roche, NIH, Pfizer, Sanofi-Aventis Pharmaceuticals, Consultant for: Actelion Pharmaceuticals US, Bayer, Bristol-Myers Squibb, Boehringer Ingelheim, Chemomab, Corbus, Covis, Cytori, Eicos, EMD Serono, Genentech/Roche, Pfizer, Gilead, GlaxoSmithKline, Sanofi-Aventis Pharmaceuticals, and UCB Pharma, M. Matucci-Cerinic Grant/research support from: Pfizer, Bristol-Myers Squibb, Actelion, UCB Pharma, Consultant for: Actelion, Bayer, ChemomAb, Genentech/Roche, Inventiva, Lilly, Pfizer, J. Pena Employee of: Bayer HealthCare Pharaceuticals Inc, J. Pope Grant/research support from: Actelion, Bayer AG, Bristol-Myers Squibb, Merck, Pfizer Inc, Roche, Consultant for: Actelion, Bayer AG, Bristol-Myers Squibb, Merck, Pfizer Inc, Roche, O. Distler Grant/research support from: Actelion, Bayer, Biogen Idec, Boehringer Ingelheim, ChemomAb, EspeRare Foundation, Genentech/Roche, GlaxoSmithKline, Inventiva, Lilly, Medac, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Novartis, Pfizer, Sanofi, Sinoxa, and UCB in the area of potential treatments of scleroderma and its complications. Patent mir-29 for the treatment of systemic sclerosis licensed, Consultant for: Actelion, Bayer, Biogen Idec, Boehringer Ingelheim, ChemomAb, EspeRare Foundation, Genentech/Roche, GlaxoSmithKline, Inventiva, Lilly, Medac, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Novartis, Pfizer, Sanofi, Sinoxa, and UCB in the area of potential treatments of scleroderma and its complications. Patent mir-29 for the treatment of systemic sclerosis licensed